Identifying Analytical Thinking Skills in Forestry Students: Understanding Climate Change Awareness in the 21st Century Context - Muhali Muhali; Hulyadi Hulyadi; Khaeruman Khaeruman; Gargazi Gargazi; Irham Azmi (Universitas Pendidikan Mandalika, 2025)
Climate change is a critical global issue with complex and far-reaching impacts that extend beyond the environment to include social, economic, and health dimensions. Addressing these challenges requires future professionals, such as forestry students, to develop strong analytical thinking skills, particularly in identifying and formulating environmental problems. Despite the growing recognition of climate change, limited research exists on forestry students’ understanding and analytical response to this issue, especially within specific regional contexts such as West Nusa Tenggara (NTB), Indonesia—a region particularly vulnerable to climate-related effects. This study aims to examine the level of awareness among forestry students regarding climate change issues in NTB and to evaluate their problem-identification and problem-formulation skills based on the phenomenon of global warming in the area. The novelty of this research lies in its regional focus, as NTB is seldom featured in climate literacy studies despite its unique climatic challenges. Using a descriptive quantitative method, data were collected from 26 forestry students enrolled in a Basic Chemistry course through an essay-based test administered in October. The variables observed were environmental awareness, problem-formulating ability, and problem-identifying ability. Data analysis was conducted descriptively and presented in tables and graphs. Results showed low student performance across all variables, with mean scores of 44.6 (awareness), 50.96 (problem formulation), and 40.76 (problem identification). These findings underscore the urgent need for strategic, problem-based educational approaches to improve students’ climate awareness and analytical competencies, ultimately preparing them to effectively contribute to sustainable environmental solutions in their future professional roles.